Creativity in the primary classroom - Desailly, Juliet (London : SAGE, 2012)
"Creativity is an integral element of any primary classroom. It has been never more important for teachers to involve children in their own learning and provide a curriculum that motivates and engages. Being creative involves generating new ideas, reflecting upon and evaluating different teaching approaches, and establishing an environment that supports creativity. Creativity in the Primary Classroom explores how to develop as a creative teacher and how to foster creativity in your classes. Drawing from key literature and detailed real-life examples, Juliet Desailly puts into practice her extensive experience planning, advising and developing creative approaches to teaching and curriculum planning. This book examines what creativity in a primary classroom can look like, and is supported throughout by practical activities for use across curriculum subjects and reflective tasks encouraging critical engagement with key conceptual issues. This is essential reading for students on primary initial teacher education courses including undergraduate, graduate, and employment-based routes into teaching, and also for practicing teachers wishing to enhance their own teaching."--Publisher's website.
What is creativity. The key elements of creativity -- Creativity in education: history and theoretical background -- A creative child in a creative classroom. Building the skills to work creatively -- Establishing the ethos -- A creative teacher. What makes a creative teacher? -- Key skills for the creative teacher -- A creative curriculum. Planning for creative outcomes -- Medium term planning for creative outcomes -- Case studies: creativity in practice.
Includes bibliographical references (p. [153]-157) and index.
Keywords: Creative teaching; Elementary school teaching